1998
DOI: 10.1097/00007632-199801010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid Osteoma and Osteoblastoma of the Spine

Abstract: The findings support the concept that scoliosis is secondary to asymmetric muscle spasm in patients with spinal osteoid osteoma or osteoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Adolescence is regarded as the peak age for osteoid osteoma and spinal involvement has been reported as 10% to 20% in various studies [8,9]. Backache, which depends on the nidus locus, was the patients' most serious complaint.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is regarded as the peak age for osteoid osteoma and spinal involvement has been reported as 10% to 20% in various studies [8,9]. Backache, which depends on the nidus locus, was the patients' most serious complaint.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing number of reports, including our experience exemplify the utility of preoperative embolization. Anecdotally, only one report of local recurrence in 16 cases (6.25%) has been described [2,14,19,21]. The use of preoperative embolization in our patient decreased bleeding and improved visualization.…”
Section: Discussionmentioning
confidence: 61%
“…These symptoms are often present for greater than 12 months prior to diagnosis, and many patients will go on to manifest neurological sequelae or a painful scoliosis [1,[15][16][17]19]. Delayed diagnosis occurs because initial symptoms are often nonspecific and osteoblastoma accounts for less than 1% of all bone tumors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although lesions have been reported to be in concave side of deformity in almost all cases including ours, Saifuddin et al [29] reported 3 cases of convex side lesions. As shown in Table 6, there was spinal deformity in 65% of our cases (13 of 19 cases) and 12 of them (60%) were scoliosis with an average of 21.5° Cobb.…”
Section: Discussionmentioning
confidence: 67%
“…Saifuddin et al [29] reported that the thoracic and lumbar regions are the most common sites of involvement.…”
Section: Discussionmentioning
confidence: 99%